Prevalence of Anaerobic Bacteria (P.gingivalis) as Major Microbial Agent in the Incidence Periodontal Diseases by Meta-analysis - Mohammad Rafiei; Faezeh Kiani; Kourosh Sayehmiri; Fatemeh Sayehmiri; Mostafa Tavirani; Majid Dousti; Abdolkarim Sheikhi (Shiraz University of Medical Sciences, 2018)
Statement of the Problem: Periodontal diseases are complex oral diseases characterized by bacterial-induced inflammatory destruction of tooth-supporting tissues. Porphyromonas gingivalis (P. gingivalis) is a common gram-negative anaerobic oral bacteria strongly associated with periodontal disease. Purpose: The present study was conducted to estimate prevalence of P. gingivalis in patients with periodontal diseases by using meta-analysis method. Martials and Method: Different databases including PubMed, EmBase, Scopus, the Institute for Scientific Information (ISI) Web of Science, and the Cochrane Library were searched to identify original English-language studies addressing prevalence of P. gingivalis in periodontal diseases up to December 2014. The random effects model was applied in the meta-analysis and the heterogeneity between studies was assessed using a Cochran test and the I2 index. Funnel plots and Egger test were used to examine publication bias. Statistical analyses were performed using STATA version 12. Results: Forty-two eligible studies published during 1993- 2016 were selected for meta-analysis. Considering all the included studies, the total sample size was 5,884 individuals containing 2,576 healthy people with a mean age of 37.21±7.45 years and 3,308 periodontal patients with a mean age of 44.16±8.35 years. Overall, the prevalence of P. gingivalis was 78% [95% CI: 74-81] in periodontal diseases group and 34% [95% CI: 26-41] in healthy individuals. There was a significantly higher prevalence of P.gingivalis in individuals with periodontal diseases compared to healthy subjects [78% versus 34%, respectively]. Conclusion: This study indicates that P. gingivalis is highly present in subjects with periodontal diseases and it also appears in periodontally healthy people, although to a lesser extent. Thus, the presence of P. gingivalis increases the chance of periodontal disease and it can be considered as a main potential risk factor.